Analisis Prediksi Kebangkrutan Dengan Menggunakan Metode Altman Z-Score (Studi kasus pada PT. Acset Indonusa Tbk dan PT. Nusa Kontruksi Enjiniring Tbk) - Mutiara Kinanti; Dea Putri Anggraini; Ratih Kusumastuti (Sekolah Tinggi Ilmu Ekonomi Trianandra, 2023)
This study aims to determine the bankruptcy prediction of PT Acset Indonusa tbk and PT Nusa Kontruksi Enjiniring tbk in 2021 using the Altman Z-Score method. The data source used is secondary data, namely in the form of Published Financial Reports of Companies issued by the Indonesia Stock Exchange. This study uses a quantitative descriptive method. The technique used is the Altman Z-Score bankruptcy prediction model with the calculation results that the two companies are in unfavorable results or a dangerous zone so that the two companies are predicted to experience bankruptcy.